Pengenalan Indahnya Keragaman Budaya Negeriku Melalui Media Pembelajaran Mobuya - Tri Syamsijulianto; Arif Hidayat; Mohammad Zainudin (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: The Mobuya learning media stands for monopoly based culture. The Mobuya media teaching is a game based on students’ ability to play and learn, its main content is question card that point to the HOTS. The purpose of this study to introduced the beautiful cultural diversity of country through the Mobuya learning media. Methods of media development in the study are ADDIE models (analyze, design, development, implementation, and evaluation). The results of the validation of qualified silabus scholars and material in the learning media fit valid or worthy criteria with small recensions. Results of the materials validation on the silabus validation sheet, scores obtained from the silabus validation valid or worthy criteria are used with small recensions. The location of the Mobuya scientific silabus learning aim higher level of thought ability or HOTS (Higher, Order, Thinking, Skills) posed. The validation of the media given to the validator of the learning media experts show good criteria so it can be continiue but with a few part that must be revised. The achievement assesment results given to teacher show the learning media can or deserve given to learners. The Mobuya learning media test, the learning media needs to be re-perfected so that in learning it is easy for learners to use.Abstrak: Media pembelajaran Mobuya merupakan singkatan dari monopoli berbasis budaya. Media pembelalajaran Mobuya merupakan permainan yang berlandaskan kepada kemampuan siswa dalam bermain dan belajar, konten utamanya berupa kartu pertanyaan yang terarah pada soal HOTS. Tujuan penelitian ini adalah mengenalkan indahnya keragaman budaya negeriku melalui media pembelajaran Mobuya. Metode pengembangan media dalam penelitian ini adalah model ADDIE (analyze, design, development, implementation, and evaluation). Hasil validasi ahli materi silabus kevalidan materi dalam media pembelajaran sesuai dengan kriteria valid atau layak digunakan dengan revisi kecil. Hasil validasi ahli materi pada lembar validasi silabus, skor yang diperoleh dari validasi silabus kriteria valid atau layak digunakan dengan revisi kecil. Letak dari scientific silabus media pembelajaran Mobuya, arahkan kemampuan berpikir tingkat tinggi atau HOTS (Higher, Order, Thinking, Skills) ditampakkan. Validasi media yang diberikan kepada validator ahli media pembelajaran menunjukkan kriteria baik sehingga dapat dilanjutkan, tetapi dengan beberapa bagian yang harus direvisi. Hasil penilaian angket yang diberikan kepada guru menunjukkan media pembelajaran dapat atau layak untuk diberikan kepada peserta didik. Uji coba media pembelajaran Mobuya, media pembelajaran perlu disempurnakan kembali sehingga dalam pembelajaran mudah untuk digunakan oleh peserta didik.